First-order phase transitions in lattice bilayers of Janus-like particles: Monte Carlo simulations - Borówko, M.; Patrykiejew, A.; Rzysko, W.; Sokołowski, S. (Condensed Matter Physics, 2016)
The first-order phase transitions in the lattice model of Janus-like particles confined in slit-like pores are studied. We assume a cubic lattice with molecules that can freely change their orientation on a lattice site. Moreover, the molecules can interact with the pore walls with orientation-dependent forces. The performed calculations are limited to the cases of bilayers. Our emphasis is on the competition between the fluid-wall and fluid-fluid interactions. The oriented structures formed in the systems in which the fluid-wall interactions acting contrary to the fluid-fluid interactions differ from those appearing in the systems with neutral walls or with walls attracting the repulsive parts of fluid molecules.